Experimental study of six-stroke engine for heat recovery - Lukman Nul-Hakem, Mohd Yusop (2012)
This thesis describe about modifying of engine from four stroke engines to six stroke engines. Two more additional strokes are the fifth stroke, which called water injection stroke while the last stroke is called exhaust stroke. Besides, the stroke engine also known as engine two-stroke, four-stroke and also six-stroke which are new things for us. Some modification has to do at the conventional four-stroke to six-stroke. Whereas some of them are modification at the camshaft, which is gear to contact between camshaft and crankshaft with ratio 3:1, shape of plunger, head cover engine and add more other components such as water injector and pump to make the system operate well. After the modification, performance results outcomes are compare with the conventional four-stroke engines. Unfortunately, this engine is not running as well as expected when some problems occur at few part of the engine. To fix the entire problems, analysis has been undertaken to improve some part of the followers, especially since his main problems in their engines. For the future work, the follower must be upgrading the level to get the best design and strength to make sure this engine running well.